2014
DOI: 10.1136/bmjopen-2013-004369
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density, rib pain and other features of the female athlete triad in elite lightweight rowers

Abstract: ObjectiveTo determine bone mineral density (BMD) and the associations among BMD, menstrual history, disordered eating (DE), training history, intentional weight loss (IWL) and rib pain for the first time in female lightweight rowers.Setting9 lightweight rowing clubs, UK.Participants29 Caucasian female lightweight rowers volunteered. 21 (12 active, 9 retired) completed the study. Inclusion criteria: female lightweight rowers aged over 18 years. Exclusion criteria: participants with a history of bone disease, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 64 publications
2
15
1
Order By: Relevance
“…On the other hand, contrary to our hypotheses, the BMD of the C/P-RIR group was not significantly different from the BMD of both the C + P-IR and the C + P-R group at all sites. These results largely support the findings of other investigators, which demonstrated that female athletes with a history of menstrual irregularity had lower BMD [7] or Z-scores [28] at the lumbar spine but not at the femoral neck when compared with eumenorrheic athletes. Using a study design similar to that in the current study, Drinkwater et al [3] also demonstrated that athletes with current and past menstrual irregularity and athletes with episodes of menstrual irregularity interspersed with periods of menstrual regularity had lower lumbar spine BMD than athletes who had consistently regular menstrual cycles.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…On the other hand, contrary to our hypotheses, the BMD of the C/P-RIR group was not significantly different from the BMD of both the C + P-IR and the C + P-R group at all sites. These results largely support the findings of other investigators, which demonstrated that female athletes with a history of menstrual irregularity had lower BMD [7] or Z-scores [28] at the lumbar spine but not at the femoral neck when compared with eumenorrheic athletes. Using a study design similar to that in the current study, Drinkwater et al [3] also demonstrated that athletes with current and past menstrual irregularity and athletes with episodes of menstrual irregularity interspersed with periods of menstrual regularity had lower lumbar spine BMD than athletes who had consistently regular menstrual cycles.…”
Section: Discussionsupporting
confidence: 82%
“…Using a study design similar to that in the current study, Drinkwater et al [3] also demonstrated that athletes with current and past menstrual irregularity and athletes with episodes of menstrual irregularity interspersed with periods of menstrual regularity had lower lumbar spine BMD than athletes who had consistently regular menstrual cycles. However, contrary to our findings and those of other investigators [7,28], Drinkwater et al [3] reported that BMD at a weight-bearing site, the femoral shaft, was lower among athletes with current and past menstrual irregularity compared with athletes who had always had regular menstrual cycles (and compared with those who had episodes of amenorrhea/oligomenorrhea interspersed with period of eumenorrhea).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…High impact sports increases BMD at loaded sites with low impact sports having largely neutral findings [1]. The influence of high level rowing training has not been well explored with relatively small samples within a single category or discipline [25]. …”
Section: Introductionmentioning
confidence: 99%